Early identification of NORSE and transfer to care setting with appropriate supports: A proposed algorithm - Vinette, Sarah A.; Young, Gordon Bryan; Khosravani, Houman (Frontiers in Neurology, 2023)
New-onset refractory status epilepticus (NORSE) is a clinical presentation where an individual develops refractory status epilepticus without active epilepsy, or related neurological conditions. A subset of these individuals has a preceding fever and would be diagnosed with febrile infection-related epilepsy syndrome (FIRES). The underlying etiology of this condition varies and includes autoimmune and viral encephalitides. These conditions require multiple specialized health care teams working collaboratively and specific resources for investigation of the underlying etiology and management to provide optimal patient care. In this paper, we provide: (1) recommendations upon early recognition of NORSE and FIRES, (2) guidance on the resources needed to optimally provide care, and (3) guidance on considerations to initiate transfer of patients to a more specialized medical center. Additional recommendations for resource-austere centers without the ability to transfer such patients are also discussed. These recommendations are only for adult patients with NORSE as pediatric patients may require additional special considerations.